A Real-World Data Derived Pharmacovigilance Assessment on Drug-Induced Nephropathy: Implication on Gaps in Patient Care - Kim, Yujin; Choi, Chang Young; Sunwoo, Yongjun; Go, Chaerin; Kim, Semi; Eom, Sae Hyun; Shin, Sooyoung; Choi, Yeo Jin (Healthcare (Switzerland), 2024)
This retrospective cross-sectional study aims to investigate the prevalence and seriousness of drug-induced nephrotoxicity and to identify clinical predictors intensifying the seriousness of nephrotoxicity. Adverse drug events (ADEs) reported to the Korean Adverse Event Reporting System Database (KAERS DB) from January 2012 to December 2021 were investigated. The association between the seriousness and the etiologic drug was estimated in reporting odds ratio (ROR) based on disproportionality analysis. Logistic regression was utilized to recognize predictors associated with serious nephrotoxicity. The majority of ADEs were reported in ages 30 to 59, and immunosuppressants were the most etiologic medications. ADEs involving antibiotics, including vancomycin (ROR 0.268; 95% CI 0.129–0.557), were less likely to be serious. More than 93% of cyclosporine-related ADEs were serious nephrotoxicity, whereas tacrolimus was less likely to report serious nephrotoxicity (ROR 0.356; 95% CI 0.187–0.680). The risk of serious nephrotoxicity was decreased with aging (ROR 0.955; 95% CI 0.940–0.972) while increased in women (OR 2.700; 95% CI 1.450–5.008). Polypharmacy was associated with increased risk of interstitial nephritis (OR 1.019; 95% CI 1.001–1.038). However, further studies investigating the impact of clinical practice on ADE incidences as well as clinical prognosis related to nephrotoxicity are obligated.
Keywords: antibiotics; drug safety; gaps in patient care; immunosuppressants; KAERS DB; nephrotoxicity; pharmacovigilance; real-world data